The effect of sustainable leadership in entrepreneurial performance: Analytical research - Hamid Diad * , Sara; Adel Hamed, Suhair (Journal of Economics and Administrative Sciences, 2024)
The current research aims to test the relationship and effect of sustainable leadership its dimensions (cohesive diversity, organizational justice, employee development, progress and advancement, and work-life balance) as independent variables on entrepreneurial performance with its dimensions (creativity and innovation, reputation, proactiveness, self-evaluation) as dependent variables in the Ministry of Science and Technology. Additionally, the study seeks to identify the levels of availability and utilization of sustainable leadership that are more suitable for the current conditions in the ministry. The research aims to provide a set of recommendations contributing to the enhancement of the practice and adoption of the variables within the researched organization. Adopting a descriptive-analytical approach, the research collected data from 172 respondents representing various positions within the ministry (general manager, assistant general manager, center manager, department manager and section head). The data collection methods included a questionnaire with 48 items, supplemented by personal interviews and field observations as supporting tools. The researcher utilized statistical programs (Excel, SPSS V.28), employing appropriate statistical methods such as normal distribution tests, factor analysis, exploratory and confirmatory analysis, mean, percentage, standard deviation, and relative importance to test the hypotheses. The results indicate that the Ministry of Science and Technology has embraced sustainable leadership practices, demonstrating its inclination toward adopting its dimensions, including organizational justice, cohesive diversity, employee development, progress and advancement, and quality of work life, leading to an improvement in its entrepreneurial performance. Research paper